Beyond Crimea the new Russian empire - Grigas, Agnia 1979- (Yale University Press, 2016)
How will Russia redraw post-Soviet borders? In the wake of recent Russian expansionism, political risk expert Agnia Grigas illustrates how - for more than two decades - Moscow has consistently used its compatriots in bordering nations for its territorial ambitions. Demonstrating how this policy has been implemented in Ukraine and Georgia, Grigas provides cutting-edge analysis of the nature of Vladimir Putin's foreign policy and compatriot protection to warn that Moldova, Kazakhstan, the Baltic States, and others are also at risk